Implementation of Immigration Policy for Mixed Marriage Couples in Gorontalo Province - Piu, Lysa; Sulila, Ismet; Hamim, Udin (Abdurrauf Science and Society, 2025)
Policy dimension is one of the vital components in public administration that influences the success of government policy implementation. Keban (2014) emphasized that policies must be based on accurate data and through a participatory formulation process, to ensure that the policy is able to answer the problems faced by the community. In this case, policies must always place the community as the main priority, by paying attention to social justice and inclusiveness in the formulation process. This study uses a qualitative approach with a descriptive method. This approach was chosen because this study seeks to understand in depth how the Implementation of Immigration Policy for Mixed Marriage Couples in Gorontalo Province is going well. The qualitative approach allows researchers to explore the perspectives of various stakeholders, such as mixed marriage couples and immigration officers.Based on the research results, it can be concluded that although the immigration procedures implemented at the Class I TPI Gorontalo Immigration Office are quite clear and structured, there are still several obstacles faced by mixed marriage couples, both in administrative, legal, and social aspects.